Pedagogical Conditions And Mechanisms Of Development Of Social Active Civil Competence In Students - Abduganiev Ozod Tursunboy oglu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses development of active civic initiatives, education of students as intellectually competent individuals, pedagogical conditions for the development of socially active civic competence, approaches to the concept of the essence of civic, active citizenship, individual approach to education, socially active civic education , the desire to participate in the political life of the state, to have an active civic position, the role of the state and society in human life is interpreted differently, the role of socially active civic education in a democratic society, the development of socially active civic competencies students feel involved in society free democracy through active participation in the changes taking place in the life of the society, knowledge of one's civic duties, responsibilities and rights, observance of them, treatment of legal relations and legal culture development of students as professionals in the process of building a democratic state, civil society, through the means of pedagogical and psychological influence.